Edukasi Persiapan Psikologi Pada Wanita Usia Subur Untuk Masa Prakonsepsi - Kadir, Arisna; Dahniar, Dahniar; Purnama Sari, Lili; Hasnaeni, Hasnaeni; Firawati, Firawati (Karya Kesehatan Journal of Community Engagement, 2024)
Data from the World Health Organization (WHO) shows that around 10% of pregnant women and 13% of new mothers experience mental disorders, especially depression. In developing countries this figure is even higher, at 15.6% during pregnancy and 19.8% after childbirth. To prevent similar cases, it is necessary to prepare for pregnancy which can be done during the preconception period, namely the treatment period before pregnancy occurs with a time span of three months to one year before conception. Therefore, Education on Psychological Preparation of Women of Fertile Age for Preconception Preparation at the Bara-Barayya Health Center through community service activities is considered necessary with the aim of changing the views of women of childbearing age and families related to psychological health and behavior that can affect it as an effort to prepare for preconception. The method used was lecture and question and answer. The participants who attended the counseling consisted of 23 people where the post-test evaluation showed the participants' better understanding of efforts to maintain mental health can help mothers prepare for pregnancy in the preconception period. Conclusion: counseling participants, namely women of childbearing age, understand the importance of psychological preparation during the preconception period